Metode Pengajaran Nahwu Shorof; ber-Kaca dari Pengalaman Pesantren - Limas Dodi (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2013)
Shorof nahwu science teaching methods that can not be separated from the traditional system while the system is a departure from the traditional pattern of teaching is very simple and in the first onset, is teaching sorogan, bandongan and wetonan in studying religious books written by the scholars of the medieval era and the book these books are known term yellow book. Nahwu is Tata-Arabic (Arabic Grammar), whereas according lughot Shorof or etymology is changing, being according to the origin of the term is changing the shape of the other forms to achieve the desired meaning that can only be achieved with the change. Shorof nahwu science teaching methods can not be separated from the traditional system, which departs from the pattern of teaching is very simple and in the first onset, is teaching sorogan, bandongan and wetonan. In addition, Drs. H. M Sulthon Masyhud, M Pd added in addition to the usual method sorogan, bandongan and wetonan he added the rote method, and some are using musyawaroh method